In-situ observations of damage-fracture evolution in surrounding rock upon unloading in 2400-m-deep tunnels - Guo, Haosen; Sun, Qiancheng; Feng, Guangliang; Li, Shaojun; Xiao, Yaxun (International journal of mining science and technology, 2023)
The damage-fracture evolution of deep rock mass has obvious particularity, which is revealed in 2400-m-deep tunnels by field tests. The evolution of the excavation damaged zone depth is consistent with that of the fractured zone depth. The ratio of the excavation damaged zone depth to the excavation fractured zone depth is greater than 2.0 in a rock mass with both high strength and good integrity, but less than 1.5 in a rock mass with lower strength or poor integrity. Zonal disintegration in a rock mass with high strength and fair integrity is more likely to occur when it contains more than two groups of primary fractures in damaged zones. Fractures develop outward in zonal disintegration but are totally different from the single-zone fracture, in which the fractures develop inward, and it is the starting position of the fractured zone when the excavation surface of the middle pilot is 7–9 m close to the pre-set borehole and it stops after the excavation surface of the baseplate is 11–14 m away. The most intense evolution occurs around 2–4 m from the pre-set borehole in the sidewall expansion stage. The research results provide a reference for the monitoring scheme and support design of CJPL-III in its future construction.